7y+2y(y-2)=6(y+1)-2

Simple and best practice solution for 7y+2y(y-2)=6(y+1)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7y+2y(y-2)=6(y+1)-2 equation:



7y+2y(y-2)=6(y+1)-2
We move all terms to the left:
7y+2y(y-2)-(6(y+1)-2)=0
We multiply parentheses
2y^2+7y-4y-(6(y+1)-2)=0
We calculate terms in parentheses: -(6(y+1)-2), so:
6(y+1)-2
We multiply parentheses
6y+6-2
We add all the numbers together, and all the variables
6y+4
Back to the equation:
-(6y+4)
We add all the numbers together, and all the variables
2y^2+3y-(6y+4)=0
We get rid of parentheses
2y^2+3y-6y-4=0
We add all the numbers together, and all the variables
2y^2-3y-4=0
a = 2; b = -3; c = -4;
Δ = b2-4ac
Δ = -32-4·2·(-4)
Δ = 41
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-3)-\sqrt{41}}{2*2}=\frac{3-\sqrt{41}}{4} $
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-3)+\sqrt{41}}{2*2}=\frac{3+\sqrt{41}}{4} $

See similar equations:

| 74−59=75−x | | 8(x-1)=8x=5 | | 22x^2-20x+4=(5x-2) | | 50n+80=40n+100 | | 4206/180=x | | 6=2u+4(u+3) | | -6y-14=8y+14 | | 33-4x=19+10x | | 20n+80=10n+120 | | (12)x/3+(12)3x/4=(12)2 | | 29-7x=10+12x | | 5/7=p+4/7​ | | 176=92-y | | X=x÷4+9 | | v2=465 | | 2x-16+2x+1+8=180 | | 3(-5+b)=-42 | | x-5=3x=1 | | 3x-27=2x+34 | | 10-8x-7-13x=6 | | 0=21x-4.9x^2-8 | | 1/3x-2=-1/2+8 | | 10=4+-j | | 2g−g=3 | | 7(w-3)-3w=15 | | 28-7x=11+10x | | 45/7.5=x/30 | | (5-x)(x-4)=20-3x | | 1/10y+4=-14 | | 11x-1+13x-5+90=180 | | 44=y/3+14 | | 8(x-4)=34 |

Equations solver categories